MENUJU MASYARAKAT BERDAYA: MEMBEDAH PENDEKATAN SELF-HELP DAN TECHNOCRATIC PADA DESA SIDOSERMO DAN DESA BATU MALANG - Al Haniva, Sophia; Putri Dewanti, Arinta (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The community empowerment approach is a major factor in policy-making to implement development that involves the community. As carried out by Diskumdag Batu City in the village in Batu City Malang which empowers its community through SMEs. In addition, Sidosermo Indah Surabaya Village also carried out a strategy to increase the potential of its village through a special needs community called "Tiara Handycraft". This research aims to compare the use of community empowerment approaches in Batu Malang City and Sidosermo Indah Village. This research uses a literature study research approach with the Systematic Literature Review method. Primary data sources include journals and related studies, while secondary data comes from supporting books and e-books. The results showed that SME development and training conducted by Diskumdag Batu City were approved by the community. Meanwhile, the Tiara Handicraft business in Sidosermo Indah Village, Surabaya takes a self-help and technocratic approach that implements changes and reforms that start from an external action that imposes a program unilaterally, and carries out democratic principles based on the placement of humanist empowerment that recognizes the existence of humans as active and creative beings.